Waste matters in planning - an analysis of the spatial implications of solid waste management in the city of Cape Town - Chitapi, Simba (School of Architecture, Planning and Geomatics, 2014)
Urban planning has traditionally been involved with the management of space, creation of place. It is a profession concerned with coordinating relationships between society and nature to foster development which improves all lives especially those of the poor. As such, planning synthesises the concerns of many different fields. Solid waste management however seems to has not been sufficiently appreciated in terms of its spatial implications. Planning literature does not engage substantially with issues around solid waste management. However, through the many allusions to waste and by investigating solid waste literature spatial issues emerged. Indeed, the literature unveiled two overarching themes: First, urban waste can no longer be hidden from waste generator by exporting it to the hinterland. Following on from this, a decentralisation of waste management facilities is pivotal in achieving the participation and fostering the cooperation necessary to create cyclical urban waste flow. Thus beginning with the premise that solid waste concerns are poorly addressed by planning, this dissertation investigates the reason this has transpired in Cape Town and proposes planning interventions that would begin to engender change. After conducting a spatial analysis of the City, engaging urban professionals in conversation, statistical analyses of waste flows, and reviewing the policy relationship between solid waste and spatial planning analysing, it emerged that the oversight of solid waste in planning is rooted in an uncertainty of how to address solid waste concerns. The utility of people-infrastructure relationships, the way in which urban functions relate and the link between regulatory planning policy have been underestimated in in their capacity to effect waste minimisation. In light of this, policy and spatial interventions are proposed; these aim to harness the potential of people and to increase the functionality of infrastructures. These interventions aspire to dissolve the spirit of deference - planning to SWM; citizens to SWM; urban to hinterland - evident in urban solid waste management. If successful, these interventions should challenge urban perceptions of waste such that waste is no longer the responsibility of 'the other'; through recognition of waste's utility a sense of personal responsibility may develop. So, once planning as a profession 'owns' waste management as a key concern, planning can contribute to changing perceptions.